Mid-Holocene pulse of thinning in the Weddell Sea sector of the West Antarctic ice sheet - Hein, Andrew; Marrero, Shasta; Woodward, John; Dunning, Stuart; Winter, Kate; Westoby, Matt; Freeman, Stewart; Shanks, Richard; Sugden, David (Nature Communications, 2016)
Establishing the trajectory of thinning of the West Antarctic ice sheet (WAIS) since the last glacial maximum (LGM) is important for addressing questions concerning ice sheet (in)stability and changes in global sea level. Here we present detailed geomorphological and cosmogenic nuclide data from the southern Ellsworth Mountains in the heart of the Weddell Sea embayment that suggest the ice sheet, nourished by increased snowfall until the early Holocene, was close to its LGM thickness at 10 ka. A pulse of rapid thinning caused the ice elevation to fall ~400 m to the present level at 6.5–3.5 ka, and could have contributed 1.4–2 m to global sea-level rise. These results imply that the Weddell Sea sector of the WAIS contributed little to late-glacial pulses in sea-level rise but was involved in mid-Holocene rises. The stepped decline is argued to reflect marine downdraw triggered by grounding line retreat into Hercules Inlet.